Entrepreneurial intention among business undergraduate student in UUM - Nur Hazwani, Abdullah (2018)
The number of a young entrepreneur that involved in business remains low, it is important to investigate the entrepreneurial factors to attract the university student to venture business involved. The main objective of this study is to analyse the relationship between personal attitude, perceived feasibility, personal traits and entrepreneurial knowledge with the entrepreneurial intention among the undergraduates under the School of Business Management, Universiti Utara Malaysia. Data was collected by using the questionnaire that has been distributed to 302 respondents; however, only 200 questionnaires have been successfully collected for the data analysis. Findings of the research revealed that only two (2) out of four variables having significant relationship with the entrepreneurial intention, which are personal attitude and personal traits. The recommendation for the related stakeholders and future research were also discussed.